P 26. Ipsilateral silent period in multiple sclerosis and healthy controls depends on stimulus intensity. Issue 8 (August 2021) - Nafz, C.; Seusing, N.; Lotze, M.; Strauss, S.; Grothe, M.
Abstract : Background. In patients with multiple sclerosis (MS) lesions of the corpus callosum can be found even at early disease stages. With transcranial magnetic stimulation (TMS) the transcallosal interhemispheric inhibition can be investigated using the ipsilateral silent period (ISP). Various studies revealed differences in the duration of ISP in MS-patients compared to healthy controls (HC), both as increased (Schmierer et al. 2002) or decreased (Lenzy et al., 2007), presumably because of methodological differences in stimulus intensities. Therefore this study aimed to investigate the influence of stimulus intensities on the ISP in MS compared to HC.Methods: 20 MS (13 females, age: 44.6 ± 10.6) and 15 HC (9 females, age: 41.4 ± 10.0) matched by age and sex received a structural cranial MRI to perform MR-navigated TMS of the motor cortex. In total 40 TMS pulses were applied and durations of ISP were estimated in each participant. To examine to which extent the intensity of the TMS pulses modulate the duration, measurements were repeated at four stimulus intensities (state 1 to 4, 10 stimuli per state) calculated by the individuals resting motor threshold (RMT; 1.2 RMT/1.5 RMT/1.75 RMT/2 RMT). Results. rmANOVA revealed an effect for ISP-duration (RMT intensities; p < 0.05) but no significant group effect (MS, HC; n.s.). Post hoc analyses for RMT showed significant increase in duration between 1.2 and 1.5 RMT ( p < 0.05). Conclusion. Our data provide evidence that the intensity of TMS may have an impact on the resulting duration of ISP in both MS and HC, which might explain the somewhat contradictory results in the literature so far. Future studies in patient cohorts should use different stimulus intensities in ISP. References Schmierer et al., 2002. Neurology 59: 1218-24. Lenzy et al., 2007. Hum Brain Mapp 28: 636-44.